A COMPARATIVE ANALYSIS OF SPECIES COMPOSITION OF GROUND BEETLES OF COASTAL AND ISLAND ECOSYSTEMS OF THE WESTERN CASPIAN - G. M. Abdurakhmanov; G. M. Nakhibasheva; S. M. Klicheva; Z. M. Eldarkhanova (Юг России: экология, развитие, 2014)
For the first time studied the species composition of ground beetles of coastal and island ecosystems of the Western Caspian. The article provides a comparative analysis of species composition of ground beetles and adjacent areas.